2019
DOI: 10.26508/lsa.201900453
|View full text |Cite
|
Sign up to set email alerts
|

Cx3cr1-deficient microglia exhibit a premature aging transcriptome

Abstract: Gyoneva et al use RNA-seq to show that Cx3cr1-deficient microglia in young mice display a gene expression profile similar to microglia in aged mice, suggesting premature microglial aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 65 publications
3
53
2
Order By: Relevance
“…We subsequently analyzed gene expression levels of a panel of microglial markers in MDD cases (n = 68 samples derived from 25 donors) and controls (n = 66 samples derived from 19 donors). We defined three categories: (1) genes with important homeostatic properties (TMEM119 and CX3CR1) [44][45][46], (2) genes upregulated upon immune activation (IL1B and IL6), and (3) genes upregulated in responses to 'anti-inflammatory' triggers (CD163 and MRC1) [47,48]. A PCA of expression levels of those 6 selected genes showed that microglial samples segregated between MDD patients and controls ( Fig.…”
Section: Gene Expression Levels In Microglia From Mdd Patients and Comentioning
confidence: 99%
“…We subsequently analyzed gene expression levels of a panel of microglial markers in MDD cases (n = 68 samples derived from 25 donors) and controls (n = 66 samples derived from 19 donors). We defined three categories: (1) genes with important homeostatic properties (TMEM119 and CX3CR1) [44][45][46], (2) genes upregulated upon immune activation (IL1B and IL6), and (3) genes upregulated in responses to 'anti-inflammatory' triggers (CD163 and MRC1) [47,48]. A PCA of expression levels of those 6 selected genes showed that microglial samples segregated between MDD patients and controls ( Fig.…”
Section: Gene Expression Levels In Microglia From Mdd Patients and Comentioning
confidence: 99%
“…Previously, we have shown that the LysMCre-Socs3 / mice had higher levels of pSTAT3 in the retina (54). Furthermore, a recent study has shown that CX3CR1-de cient microglia exhibit a premature aging transcriptome (55). It is possible that microglia from the DKO mice may also undergo premature aging although this warrants further investigation.…”
Section: Discussionmentioning
confidence: 93%
“…In this regard, two recent studies support these results. The first one determined that Cx3cr1 −/− microglia present a lower phagocytic and migratory capacity per se [ 242 ], while the second revealed that Cx3cr1 −/− microglia of young animals are very similar to the wild type (WT) microglia of older animals [ 243 ]. On the basis of their findings, the authors of the latter study suggested that the absence of CX3CR1 confers a premature aging transcriptome to these cells, accompanied by a decrease in phagocytosis.…”
Section: Neuron–microglia Crosstalk: Implications Of the Cx3cl1–cxmentioning
confidence: 99%